ANALISIS IMPLEMENTASI STRATEGI PEMBELAJARAN AKTIF DALAM MENINGKATKAN KETERLIBATAN PESERTA DIDIK PADA PELAKSANAAN PLP II DI MAN 2 BONE - Fitria Adriana Putri Rusdi; Syamsuria; Putri Lestari; Fika; Rina Puspita Sari; Susianti; Melati; Nazwa Pasha Kahmilah; Imelda; Nur Fadila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of active learning strategies in increasing student involvement in the implementation of the School Field Introduction Program II (PLP II) at MAN 2 Bone. Active learning is a learning approach that places students as the main subject in the learning process through discussion activities, group work, problem-solving, and learning activities that encourage cognitive, affective, and psychomotor engagement. This study uses a qualitative descriptive method with data collection techniques in the form of observation, documentation, and reflection during PLP II activities. The results of the study showed that the active learning strategies applied included group discussions, questions and answers, project-based learning, and the use of technology-based learning media. The implementation of these strategies is able to create a more interactive learning atmosphere, increase student participation in learning activities, and encourage students' communication and cooperation skills. However, in its implementation, there are still several obstacles such as differences in the level of students' abilities, some students who are less active, and limitations in the optimal use of digital media. Efforts are made to overcome these obstacles through the use of more varied learning methods, a personal approach to students, and the use of interesting learning media. Based on the results of the study, it can be concluded that the implementation of active learning strategies in PLP II activities at MAN 2 Bone makes a positive contribution to increasing student involvement and becomes an important experience for prospective teacher students in developing pedagogic competencies.